Arctiini (Lepidoptera, Erebidae, Arctiinae) em áreas de savanas na áres de proteção ambiental Alter do Chão, Santarém, Pará, Brasil - VALENTE, Danúbia Marcela Pereira (Universidade Federal do Oeste do Pará, 2021)
The moths of Arctiini tribe have great diversity and abundance of species and have easy capture and are used as bioindicators in environmental monitoring. Knowledge of lepidopterofauna the Amazon region is an important point for its conservation. This work investigated the moth fauna Arctiini in savanna areas in the Environmental Protection Area Alter do Chão, Santarém, Pará. This work was divided into two chapters: The first is a faunal analysis and the second an inventory of Arctiini. The specimens were collected using light trap, Pennsylvania model, staying one night in the sampling units from 18:00 6:00. In the first chapter we analyzed the composition, abundance (N), richness (S), constancy, dominance, Shannon‘s diversity index (H ') and Shannon uniformity (U), dominance Berger Parker (BP), similarity and richness estimates (Bootstrap, Chao (1 and 2) and Jackknife (1 and 2)) and correlation between abundance and richness and meteorological variables (precipitation, air temperature and relative humidity) from June 2014 to May 2015 in two areas. The second evaluated the composition, abundance and richness from June 2014 to February 2016. The faunal analysis results were: 580 specimens (N) and 91 species (S); Pseudalus limona Shaus 1896 was abundant, constant and dominant; the diversity index showed high diversity (H '= 3.34), uniformity (U = 0.74) and low dominance (BP = 0.30); the maximum estimated richness was 134 (Jackknife 2) and a minimum 106 (Bootstrap); and significant positive correlation between abundance and relative humidity (r = 0.78 and p <0.00251). In inventory occurred 1,141 specimens (N) and 126 species (S), including three new records for the Amazon. Thus, suppose that the savanna areas of Environmental Protection Area Alter do Chão are relevant research and conservation laboratories for diversity Arctiini, recommending further studies of this taxon to expand the knowledge of the moth fauna in the Amazon.